Simulation verification for the robustness of passive compass gait with a joint stiffness adjustment. (2nd November 2019) - Kino, Hitoshi; Sakata, Kosuke; Uemura, Mitsunori; Mori, Naofumi
ABSTRACT: A passive walking robot can achieve a smooth gait without any sensory feedback while walking down a slope. This phenomenon is based on the transformation of potential energy into kinetic energy in the legs. Although the entrainment is observed in a passive gait motion, there is a possibility that the passive gait cannot be achieved in the case of variations in physical parameters, initial conditions, and disturbances. To realize a robust passive gait against variations in physical parameters, this paper proposes a passive gait system that possesses a joint stiffness adjustment. Targeting a compass model, this paper investigates the effectiveness of the proposed method for a passive gait against variations in slope angle and hip joint mass through simulation. As a result, the simulation results show that this method especially has strong robustness against the slope angle variation. GRAPHICAL ABSTRACT: